Perancangan Sistem Penentuan Peluang Usaha pada Usaha Mikro di Kota Binjai Menggunakan Metode Topsis: Studi Kasus; Dinas Koperasi & Umkm Kota Binjai - Heka Herawati Br Tarigan; Relita Buaton; Lina Arliana Nur Kadim (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
As a developing city, Binjai has a variety of business potential that can be exploited by micro entrepreneurs. However, in identifying and exploiting these opportunities, they are often faced with various obstacles, such as lack of access to market information, intense competition, and changes in consumer needs. Therefore, determining effective business opportunities is the key to the growth and sustainability of micro businesses in Binjai City. Determining business opportunities for micro businesses in Binjai City includes an understanding of the complexities and challenges faced by the MSME sector in identifying and exploiting business opportunities. Determining business opportunities requires alternative types of business in the TOPSIS method to compare various business opportunities based on important factors so that you can choose the one with the most potential and profit. In this context, the use of the TOPSIS method is important to assist in making more informed and effective decisions for authorities such as the Department of Cooperatives and MSMEs. This method will provide a systematic framework for evaluating various existing business opportunities, enabling a more objective and accurate assessment to support the development of MSMEs in Binjai City.